2020
DOI: 10.5194/egusphere-egu2020-10539
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Overview of the 2019 Sentinel-5p TROpomi vaLIdation eXperiment (TROLIX)

Abstract: <p>For the validation of Sentinel-5p/TROPOMI the TROpomi vaLIdation eXperiment (TROLIX) was held in the Netherlands based at the Cabauw Experimental Site for Atmospheric Research during September 2019. TROLIX consisted of active and passive remote sensing platforms in conjunction with several balloon-borne and surface measurements.</p><p>The intensive observations will serve to establish the quality of TROPOMI L2 main data products (UVAI, Aerosol Layer Height, NO&l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Therefore, an elevation calibration exercise was included in the campaign plan. More detailed descriptions of the CINDI-2 campaign and its objectives are given in Kreher et al (2019) and Apituley et al (2019).…”
Section: The Cindi-2 Campaign 15mentioning
confidence: 99%
“…Therefore, an elevation calibration exercise was included in the campaign plan. More detailed descriptions of the CINDI-2 campaign and its objectives are given in Kreher et al (2019) and Apituley et al (2019).…”
Section: The Cindi-2 Campaign 15mentioning
confidence: 99%
“…1). Although this work focuses primarily on the ozone lidar profiling during the study, the larger campaign overview, background and motivation can be found in Apituley et al (2019Apituley et al ( , 2020 or Kreher et al (2020).…”
Section: Introductionmentioning
confidence: 99%